2006
DOI: 10.1021/cm051516q
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and Thin Films of Bismuth Vanadates Prepared from Hybrid Materials Made from an Organic Polymer and Inorganic Salts

Abstract: A new precursor route for the preparation of bulk oxides and thin films of bismuth vanadates is proposed. The method involves the thermal treatment under air and mild conditions of hybrid organic-inorganic precursors, made from a zwitterionic salt-free polymer matrix and selected inorganic species. Monoclinic BiVO 4 was obtained in the form of bulk oxide by calcination of the powdered homogeneous hybrid materials at 600 °C, from precursors containing Bi and V in stoichiometric amounts. In the same way, thermod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…42-0135), shown in Fig. 1b, which has been synthesized and investigated for its dielectric, pyroelectric, and ferroelectric properties [1,43,52,53]. Zhou et al reported that when the pH value was higher than 9, no BiVO 4 was obtained due to the strong complex ability between Bi 3+ and OH − , with Bi(NO 3 ) 3 , NH 4 VO 3 , HNO 3 and NaHCO 3 as raw materials [42].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…42-0135), shown in Fig. 1b, which has been synthesized and investigated for its dielectric, pyroelectric, and ferroelectric properties [1,43,52,53]. Zhou et al reported that when the pH value was higher than 9, no BiVO 4 was obtained due to the strong complex ability between Bi 3+ and OH − , with Bi(NO 3 ) 3 , NH 4 VO 3 , HNO 3 and NaHCO 3 as raw materials [42].…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al reported that when the pH value was higher than 9, no BiVO 4 was obtained due to the strong complex ability between Bi 3+ and OH − , with Bi(NO 3 ) 3 , NH 4 VO 3 , HNO 3 and NaHCO 3 as raw materials [42]. Rullens et al reported that Bi 4 V 2 O 11 was prepared from hybrid material exhibiting a Bi/V molar ratio of 2, and thermodiffractometry studies indicated that Bi 4 V 2 O 11 phase could be stabilized under very soft thermal conditions (300 • C) [43]. In this experimental condition, Bi 4 V 2 O 11 phase was formed in alkaline condition adjusted by addition of Na 2 CO 3 , indicating that the alkaline condition is more beneficial to the formation of Bi 4 V 2 O 11 phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the development of new methods for the preparation of micron or submicron or nano phosphors may increase the possibilities for high effective rare earth phosphors [17][18][19][20][21][22]. For example, the sol-gel technology based on hydrolysis and polycondensation process is the most popular, which has been verified to be very useful in the synthesis of nonagglomerated nanoparticles with surface accessibility for treatments and able to be used in thin-film techniques related to the sol-gel process [23][24][25][26][27][28][29][30][31]. Besides this, chemical coprecipitation is also in common use to obtain the precursors for the preparation of luminescent materials, which is based on the wet solution chemical synthesis, just like sol-gel process [32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…creation of an organised pore volume into the mixed oxides). Thus, the impact of the presence and degradation of the copolymer matrix on the physico-chemical properties (morphology, texture, structure) and the catalysts behaviour is a key point of this study [15,16].…”
Section: Introductionmentioning
confidence: 99%